PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN DIORAMA TUGAS PEMERINTAHAN DESA UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI INFORMASI LINGKUNGAN TEMPAT TINGGAL KELAS III DI SDN PAKIS V SURABAYA - Enjelika Saputri; Lusy Tunik M; M, Ahmad Khairussyifa A (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the application of the Problem Based Learning (PBL) model assisted by the diorama media of village government tasks in improving the learning outcomes of grade III students of SDN V Surabaya on the material of understanding information related to the residential environment based on RT, RW, and village heads. The PBL model was chosen for its ability to encourage students to think critically in solving problems, while dioramas provide three-dimensional visual representations that help students understand the tasks and roles of government at the village level. The research uses the Classroom Action Research (PTK) method with two learning cycles. The results showed a significant improvement in student learning outcomes, with the percentage of classical completeness increasing from 54% in the pre-cycle to 75% in the first cycle, and 89% in the second cycle. The grade point average also increased from 68.2 in the pre-cycle to 74.6 in the first cycle, and 82.3 in the second cycle. The application of the diorama-assisted PBL model has been proven to be effective in improving students' understanding of the duties and roles of government at the village level, as well as improving their ability to identify and solve problems related to the residential environment.